Composite Hydration Process of Clay Minerals Simulating Mineral Clay Components and Influence Mechanism of Cations - Huang Siyao; Xu Mingbiao; Xu Peng; Zhang Yu; Wang Xinying (Energies, 2022)
Clay minerals are an important part of the mud shale reservoir, and their type of content has a great impact on the hydration of the formation. The hydration of clay minerals causes a decrease in drilling fluid performance, an increase in pore pressure, and a decrease in rock strength, leading to wellbore wall collapse. Therefore, it is important to study the influence of clay mineral hydration on well-wall stability. In this paper, we analyze the hydration process of clay minerals qualitatively and quantitatively by simulating the mineral clay fraction and the effect of the change in cations on their hydration and clarify the difference in the hydration of different clay minerals. The results show the following: (1) montmorillonite has the most obvious hydration and swelling effect, while the hydration of illite is mainly based on hydration and dispersion, which easily produce exfoliations and fall off in the stratum; kaolinite has poor hydration performance, while chlorite shows certain hydration but low hydration degree. (2) Cations have a certain inhibitory effect on the hydration of clay minerals, and the degree of hydration inhibition is different for different types. (3) Different clay minerals also differ in the form of state after water exposure, as montmorillonite shows swelling, while illite has no swelling, but its dispersion is stronger.